Cross-cultural adaptation and multicentric validation of the Italian version of the Simplified Evaluation of CONsciousness Disorders (SECONDs) - Bahia Hakiki; Silvia Pancani; Agnese De Nisco; Anna Maria Romoli; Francesca Draghi; Daniela Maccanti; Anna Estraneo; Alfonso Magliacano; Marcella Spinola; Cinzia Fasano; Matilde Leonardi; Martina Cacciatore; et al. (PLoS ONE, 2025)
Introduction The Coma Recovery Scale-Revised (CRS-R) is the recommended tool to assess consciousness in patients with prolonged Disorders of Consciousness (pDoC). However, the time needed to administer it may limit its use. A shorter tool has been validated: the Simplified Evaluation of CONsciousness Disorders (SECONDs). This multicentre study aimed to develop and validate a cross-cultural adaptation of the SECONDs into Italian. Methods An interdisciplinary expert team, from both Fondazione Don Carlo Gnocchi and Istituto Neurologico Carlo Besta, led the translation processes. Independent certified translators were also involved in a blinded modality. Patients diagnosed with Unresponsive Wakefulness Syndrome (UWS) or Minimally Conscious State (MCS) admitted to 3 Italian rehabilitation units were enrolled. The CRS-R and SECONDs were administered in 5 sessions over two weeks by 3 blinded examiners at each center (3 times, with 2 sessions conducted by the same examiner). Weighted Fleiss’ kappa and Spearman correlation coefficients were used to assess intrarater and interrater reliability and concurrent validity. Results Sixty adults with pDoC were assessed: 23 women; median age: 64 years; 14 trauma, median post-onset time: 2 months. Intrarater and interrater reliability showed almost perfect agreement (kappa coefficients 0.968 and 0.935, respectively; p<0.001). The comparison of CRS-R vs. SECONDs on the same day or the best out of 5 SECONDs/CRS-R led to a substantial to almost perfect agreement both for the total score of the CRS-R and the SECONDs’ Additional Index (ρ = 0.772–1.000; p<0.001) and for the consciousness diagnosis (k = 0.784–0.935; p<0.001). The disagreement rate between the overall best diagnosis of the SECONDs and the best CRS-R diagnosis was 6.7%. Conclusion The Italian version of the SECONDs has been cross-culturally adapted to serve as a shorter assessment tool for the diagnosis of pDoC. Our study shows its excellent reliability and concurrent validity when compared to the CRS-R.